2021
DOI: 10.1002/bies.202100010
|View full text |Cite
|
Sign up to set email alerts
|

How do boreal forest soils store carbon?

Abstract: Boreal forests store a globally significant pool of carbon (C), mainly in tree biomass and soil organic matter (SOM). Although crucial for future climate change predictions, the mechanisms underlying C stabilization are not well understood. Here, recently discovered mechanisms behind SOM stabilization, their level of understanding, interrelations, and future directions in the field are provided. A recently unraveled mechanism behind C stabilization via interaction of root‐derived tannins with fungal necromass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…However, given the multiple mechanisms that contribute to SOM persistence, the directionality of the effects of ErM plant and fungal traits remains unclear. For instance, interactions between plant and fungal litter inputs are thought to increase the longerterm persistence of particulate SOM through the formation of tannin-organic N complexes (Clemmensen et al, 2013(Clemmensen et al, , 2015Adamczyk et al, 2019b;Adamczyk, 2021). Further, and in contrast to the growth efficiency-recalcitrance relationship that favors the flow of more labile substrates via the microbial biomass to mineral surfaces, both labile and recalcitrant components of fungal necromass can sorb directly to mineral surfaces efficiently (See et al, 2021).…”
Section: Structural and Biochemical Traits Of Plant And Fungal Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the multiple mechanisms that contribute to SOM persistence, the directionality of the effects of ErM plant and fungal traits remains unclear. For instance, interactions between plant and fungal litter inputs are thought to increase the longerterm persistence of particulate SOM through the formation of tannin-organic N complexes (Clemmensen et al, 2013(Clemmensen et al, , 2015Adamczyk et al, 2019b;Adamczyk, 2021). Further, and in contrast to the growth efficiency-recalcitrance relationship that favors the flow of more labile substrates via the microbial biomass to mineral surfaces, both labile and recalcitrant components of fungal necromass can sorb directly to mineral surfaces efficiently (See et al, 2021).…”
Section: Structural and Biochemical Traits Of Plant And Fungal Tissuesmentioning
confidence: 99%
“…Although the humification and selective preservation models of SOM persistence have been refuted (Lehmann & Kleber, 2015), the initial biochemical traits of plant and fungal inputs – along with products arising through their decomposition – might increase the mean residence time of surface SOM pools, thereby favoring SOM accumulation under ErM plants relative to other plant mycorrhizal types (Adamczyk, 2021). For instance, ErM plants generally have higher concentrations of aromatic macromolecules, such as polyphenolic compounds and lignin, whose oxidative decomposition creates substrates with progressively more random molecular structures.…”
Section: Distinct Erm Plant and Fungal Functional Traitsmentioning
confidence: 99%
“…In addition to minerals, proteinaceous amino acids produced by microorganisms can bind to root-derived compounds, thus prolonging their presence in the environment (21). For instance, root-derived condensed tannins would transform fungal residues into more persistent forms and slow decomposition (22).…”
Section: Introductionmentioning
confidence: 99%
“…These metabolites work in concert with extracellular enzymes, and most likely ECM fungi have evolved mechanisms to keep the reactants and their products close to the hyphae. Extracellular polymeric substances (EPS) may be important functional components that assure that extracellular decomposition reactions occur at the right time and in the right place (Op De Beeck et al, 2020, 2021.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the production of fungal necromass might have a profound effect on soil C stabilization , and the release of low-molecularweight compounds by mycorrhizal fungal exudation may stimulate the decomposition activities of saprotrophic microorganisms (Phillips et al, 2012). Recent research has shown that soil C sources might be stabilized not only by association with mineral particles but also by interactions with root-derived tannins (Adamczyk, 2021). Moreover, competition with free-living saprotrophic fungi may potentially suppress SOM decomposition (the so-called Gadgil effect) (Fernandez and Kennedy, 2016).…”
Section: Discussionmentioning
confidence: 99%